2020
DOI: 10.3389/fcell.2020.555937
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of miR-7 in Gastric Cancer Is Associated With Elevated LDH-A Expression and Chemoresistance to Cisplatin

Abstract: MicroRNAs (miRNAs) are dysregulated in the context of many cancer types, making them potentially ideal diagnostic or therapeutic targets in patients in which they are aberrantly expressed. In the present study, we found miR-7 to be downregulated in gastric cancer (GC), and we further determined its expression to be closely linked to GC sensitivity to the chemotherapeutic compound cisplatin. This effect appears to be at least partially attributable to the regulation of LDH-A, which is a miR-7 target gene and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The inhibition of LDH resulted in reduced cell proliferation ( 19 ). Former research studies showed that LDH not merely associates with the activation of some proto-oncogenes, such as Myc and HIF- α ( 20 ), but also plays a crucial role in the maintenance of tumor invasiveness ( 21 , 22 ), metastatic potential ( 23 , 24 ), chemoresistance ( 25 ), and radioresistance ( 26 ). Moreover, it also showed that LDH takes part in immunosuppression ( 27 ), and LDH can be regarded as an immune surveillance prognostic marker ( 28 ) and its abnormal rise was forerunner of unfavorable outcomes in cancer patients ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of LDH resulted in reduced cell proliferation ( 19 ). Former research studies showed that LDH not merely associates with the activation of some proto-oncogenes, such as Myc and HIF- α ( 20 ), but also plays a crucial role in the maintenance of tumor invasiveness ( 21 , 22 ), metastatic potential ( 23 , 24 ), chemoresistance ( 25 ), and radioresistance ( 26 ). Moreover, it also showed that LDH takes part in immunosuppression ( 27 ), and LDH can be regarded as an immune surveillance prognostic marker ( 28 ) and its abnormal rise was forerunner of unfavorable outcomes in cancer patients ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…LDH plays an unfavorable role in various cancers; it is reportedly associated with tumor invasion and proliferation [19] , metastatic potential [20] , and drug resistance [21] . Elevated dNLR indicates a preference for granulocytes and monocytes over lymphocytes, re ecting the promotion of in ammatory dynamics in the tumor microenvironment [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Similar pathways were influenced in tongue squamous cell carcinoma [ 71 ]. Recently it was found that miR-7 could target lactate dehydrogenase A (LDH-A) in gastric cancer cells, so its downregulation can influence glycolysis, cell proliferation and sensitivity to chemotherapy [ 150 ].…”
Section: Mir-7 Role In Gastrointestinal Tumoursmentioning
confidence: 99%